Monitoring and identification of spoilage-related microorganisms in braised chicken with modified atmosphere packaging during refrigerated storage - Yang Lei; Yali Zhang; Yiqun Cheng; Jichao Huang; Ming Huang (Food Science and Human Wellness, 2023)
This study mainly monitored the dominant bacterial populations and identified the spoilage-related microorganisms of braised chicken meat stored under different CO2-modified atmosphere packaging (MAP) during refrigerated storage using a culture-dependent method and 16S rDNA identification. The quality changes and shelf life of the meat were also measured. The growth rate of total viable count (TVC) in braised chicken was slower with an increase of CO2 content in MAP, which also occurred in the remaining bacterial species monitored (lactic acid bacteria, Pseudomonas spp., Brochothrix thermosphacta). The MAP exerted beneficial effects on the quality of braised chicken, as demonstrated by retarding the production of total volatile basic nitrogen (TVB-N) and delaying lipid oxidation (TBARS test). A total of 14 isolates were identified from braised chickens with different packaging at the end of storage, these included P. fragi (6 isolates), P. psychrophila (2 isolates), Enterococcus faecalis (3 isolates), B. thermosphacta (2 isolates), Staphylococcus equorum (1 isolate).